Stabilized detection scheme of surface acoustic waves by Michelson interferometer - Mokryy, Oleh; Koshovyy, Volodymyr; Romanyshyn, Igor; Sharamaga, Roman (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A new detection scheme of surface acoustic waves by Michelson interferometer has been proposed. A substantial advantage of this scheme lies in its being stabilized against vibration and independent sensitivity of the width of an optical beam. These effects were achieved by creating an interference field on the surface of a photodetector. The measurement scheme proposed was analyzed by means of a numerical modeling method. Experiments confirming the fact of the sensitivity of the proposed detection scheme being independent of vibration and width of optical beam have also been made.
Optica Applicata, Vol. 40, 2010, nr 2, s. 449-458
Keywords: optyka; surface acoustic wave; Michelson interferometer; noncontact detection